Research on the industry applicability evaluation of the national food safety standard for Baijiu - Ting CHEN; Zhichao YANG; Yan LIU; Hongjing ZHAO; Zhiyong QIAO; Hong BAI (Zhongguo shipin weisheng zazhi, 2021)
Objective Conduct a systematic evaluation of the scientificity and practicability of the current national food safety standard for Baijiu(Chinese liquor). Methods Based on the risk analysis framework, the questionnaire surveys, business visits, expert seminars were conducted. Combined with food safety risk monitoring and supervision data, the industry applicability of the standard was systematically evaluated from three dimensions of scientificity, feasibility and necessity. Results A radar chart of evaluation has been drawn. Through the industry applicability evaluation, suggestions were made for the revision of product-specific sanitary specification and analysis method standards. Conclusion It is suggested that the hygienic standard of Baijiu should be amended and effective inspection methods should be established. At the same time, recommendations for risk assessment of the migration of nickel and chromium in liquor stored in stainless steel containers were put forward.